Bilingual Worldview in the Poetry of Oleg Mišin – Armas Hiiri: The Study of Self-Translation - Maria V. Kazakova (Studia Litterarum)
The article analyzes the interaction of two worldviews that coexist in the mind of a bilingual poet, on the example of self-translation. Finnish-Ingrian by birth, A.I. Mishin (Oleg Mishin — Armas Hiiri) begins his literary career in Karelia in the 1950s as a Russian poet. After a decade and a half of creative work in the Russian language, Mishin-Hiiri begins to publish poems in Finnish as well. The 1970s is the first stage of his bilingual work that has memory and symbolic return to the roots by learning the native Finnish language as its main theme. Being a native speaker of two languages (Russian and Finnish), the bilingual author enters the cognitive intercultural dialogue reflected in his poetic worldview that bears a mark of his national identity. The article discusses the author’s self-translations of Finnish poems into Russian, the result of the dialogic creative thinking in two languages. These self-translations are the texts semantically different from the originals. The poet not only begins to explore the possibilities of versification in two different languages but also employs different poetic images and symbols and uses different intonation. His poems and their self-translations reflect the difference in mentality of Russian and Finnish people that harmoniously co- exist in Mishin’s poetry shifting between two language systems.